Activity monitoring by multiple distributed sensing : Second International Workshop, AMMDS 2014, Stockholm, Sweden, August 24, 2014, Revised Selected Papers - Spagnolo, Paolo; Moeslund, Thomas B.; Mazzeo, Pier Luigi (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Workshop on Activity Monitoring by Multiple Distributed Sensing, AMMDS 2014, held in Stockholm, Sweden, in August 2014, as a satellite event of ICPR 2014, the 22nd International Conference on Pattern Recognition. The 9 revised full papers included in the volume investigate the challenges that arise when distributed sensor networks are used to track, monitor, and understand the activity, intent, and motives of human beings. Application areas include human-computer interaction, user interface design, robot learning, and surveillance.